IDDF2018-ABS-0107 Efficacy and safety of TENOFOVIR ALAFENAMIDE (TAF) at 96 weeks in chronic HBV (CHB) patients with risk factors for use of TENOFOVIR DISOPROXIL FUMARATE (TDF). (June 2018) - Chan, Henry Lik-Yuen; Buti, Maria; Flisiak, Robert; Ryder, Stephen; Streinu-Cercel, Adrian; Flaherty, John F; Gaggar, Anuj; Mo, Shuyuan; Mani Subramanian, G; Zoulim, Fabrian; Andreone, Pietro; Marcellin, Patrick
Abstract : Background: The recently updated EASL Guidelines for Management of HBV Infection (2017) recommend the use of TAF as an alternative to TDF in patients with risk factors unfavourable to TDF use. We, therefore, performed an evaluation of the efficacy and safety of TAF compared with TDF in patients considered to be at risk for adverse bone and/or renal effects from TDF. Methods: In two Phase 3 studies, patients (HBeAg-positive [n=873] and HBeAg-negative [n=425]) were randomised 2:1 to TAF or TDF. Antiviral efficacy (HBV DNA <29 IU/mL) and ALT normalisation (by central laboratory and AASLD criteria) were assessed by study and safety results were pooled for bone (serial DXA scans at hip/spine and serum bone biomarkers) and renal parameters (eGFR by Cockcroft-Gault [eGFRCG ] and urine biomarkers of tubular function) and assessed over 96 weeks in the subset with baseline risk factors for TDF use: Age>60 years, osteoporosis of hip or spine by t-score, eGFRCG <60 mL/min, urine albumin to creatinine ratio >30 mg/g, or serum phosphorus <2.5 mg/dL. Results: Of 1298 patients randomised and treated in the 2 studies, 239 (18%; 151 TAF and 88 TDF) patients had at least 1 risk factor for TDF use. Baseline demographics were similar between groups. At Week 96, similar antiviral efficacy (HBV DNA <29 IU/mL), and higher rates of ALT normalisation were seen in the TAF compared with the TDF group which were comparable to the overall results in these studies. Significant differences in favour of TAF were observed in key bone and renal safety parameters (table 1). Patients receiving TAF had smaller declines in BMD, particularly at the hip, and smaller changes in markers of bone resorption and formation. TAF-treated patients also showed smaller declines in eGFRCG with significantly smaller increases in markers of tubular function. Conclusions: In CHB patients considered to be at risk for TDF toxicity, TAF showed significantly less impact on bone and renal parameters while efficacy was maintained in this subgroup through 96 weeks.